Overview of registries for anaphylaxis: a scoping review protocol. Issue 5 (7th May 2021) - Stiles, Samantha L.; Roche, Ingrid; Said, Maria; Clifford, Rhonda M.; Sanfilippo, Frank M.; Loh, Richard; Salter, Sandra M.
ABSTRACT: Objective: This review will describe the scope and operational features of global registries for anaphylaxis and assess their contribution to improving knowledge and care of anaphylaxis by measuring their research output. Introduction: The incidence of anaphylaxis is increasing around the world. Structured reporting systems, such as patient registries, are needed to better understand the burden of anaphylaxis and protect the growing number of allergic patients. Inclusion criteria: The concept to be mapped is registries across the world that enroll patients who have experienced anaphylaxis. Published and gray literature sources will be considered if they describe the scope and operational features of anaphylaxis registries. Only full-text studies published in English will be included. There will be no date restriction. Methods: The JBI methodology for scoping reviews will be followed. Embase, MEDLINE, Scopus, and CINAHL will be searched from inception date for relevant articles. Identified keyword and index terms will be adapted for searches of gray literature sources, using Google advanced search functions. The authors and developers of identified registries will be contacted, where possible, to obtain additional information about the development and structure of systems. Data will be extracted by two independent reviewers. Any discrepancies will be resolved by a third reviewer. Tables and a narrative summary will be used to describe and compare the scope and features of anaphylaxis registries and outline their output to assess their contribution to research, clinical practice, and public health policy for anaphylaxis.